An Exploration of Revenue Structure Characteristics in Rural Municipalities. (March 2019) - Propheter, Geoffrey
This article tests for differences in revenue structure between small rural and nonrural municipalities. Colorado serves as a case study owing to its large number of small municipalities. Empirical analyses indicate that rural municipalities are less likely to adopt a local option sales tax, receive a smaller share of their total revenue from intergovernmental aid, and have less diversified tax systems compared to similarly sized nonrural municipalities. The article also shows these conclusions are sensitive to how one defines ruralness, indicating that what scholars know about public finance in rural communities is sensitive to the definition as well.